Zapažanja zaposlenika : uvjet unapređivanja kulture zaštite na radu - Mika, Frano (Array, 2018)
In preventing injury at work, the law provides for the application of recognized professional rules and in practice proven ways of eliminating or reducing workplace risks.Safety Hazard Observation Cards (SHOC) have proven to be a useful tool to increase employees’ awareness and attention to unsafe actions and unsafe conditions. However, in Croatian practice, it is difficult to persuade employees to write down their observations and sign them.Over the years, in the Saipem SpA Croatian Branch, we encountered employees’ reluctance towards filling the SHOC-cards. To motivate employees, we have organized events in which we set up hazards that employees should locate in the allotted time, and write and describe them on the forms, i.e. cards provided for the purpose. The employee who first identified all "set up hazards" was awarded a prize.During these events, the number of SHOC-cards written not only exceeded their annual "production" but also helped to recognize and eliminate many other hazards, and the employees were pleased to participate.The event is organized several times a year to enhance awareness of the importance of filling SHOCs and strengthening efforts to change the safety culture.